Iron deficiency and anemia are prevalent in women with multiple gestations. Issue 4 (31st August 2016) - Ru, Yuan; Pressman, Eva K; Cooper, Elizabeth M; Guillet, Ronnie; Katzman, Philip J; Kent, Tera R; Bacak, Stephen J; O'Brien, Kimberly O
ABSTRACT: Background: Little attention has been placed on the unique iron demands that may exist in women with multiple gestations. This merits attention because iron deficiency (ID) during pregnancy is associated with adverse pregnancy outcomes that are known to be more prevalent in multiple births. Objective: We characterized longitudinal changes in iron status across pregnancy in a cohort of healthy women with multiple gestations and identified determinants of maternal ID and anemia. Design: A group of 83 women carrying twins, triplets, or quadruplets (aged 20–46 y) was recruited from 2011 to 2014. Blood samples obtained during pregnancy (∼24 wk; n = 73) and at delivery (∼35 wk; n = 61) were used to assess hemoglobin, serum ferritin (SF), soluble transferrin receptor (sTfR), hepcidin, serum iron, erythropoietin, serum folate, vitamin B-12, C-reactive protein, and interleukin-6. Results: The prevalence of tissue ID (sTfR >8.5 mg/L) increased significantly from pregnancy to delivery (9.6% compared with 23%, P = 0.03). Women with depleted iron stores (SF <12 μg/L, n = 20) during pregnancy had a 2-fold greater risk of anemia at delivery, and 25% ( n = 5) developed iron deficiency anemia (IDA). Overall, 44.6% of women studied ( n = 37/83) were anemic at delivery, and 18% of women ( n = 11/61) had IDA. Erythropoietin during pregnancy was significantly negatively associated with hemoglobin at delivery. Women with erythropoietin >75th percentile during pregnancy exhibited a 3-fold greater risk of anemia, suggesting that erythropoietin is a sensitive predictor of anemia at delivery. Inflammation was present at delivery, which limited the utility of ferritin or hepcidin as iron-status indicators at delivery. Conclusions: ID and anemia are highly prevalent in women with multiple gestations. Additional screening and iron supplementation may be warranted in this high-risk population given the known associations between ID anemia and adverse maternal and neonatal outcomes. This trial was registered at clinicaltrials.gov as NCT01582802.